Pornography Consumption and Attitudes Towards Pornography Legality Predict Attitudes of Sexual Equality. Issue 3 (24th March 2021) - Speed, David; MacDonald, Jordan; Parks, Alyssa; Doucette, Hannah; Munagapati, Keerthana
ABSTRACT: Some scholars argue that the existence of pornography is an ongoing assault on women and that it should be banned. However, the existing evidence suggests the connection between pornography consumption and sexism is overstated and may actually run in the opposite direction. Using data from the General Social Survey (2010–2018), the current study investigated if "pornography consumption" and "pornography tolerance" predicted sexism and whether these associations varied by sex. Results indicated that pornography consumption predicted lower levels of sexism, although these effects were rendered nonsignificant with the inclusion of sociodemographic, religious, and sociocultural covariates. When comparing the results of the current study to findings based on data from the 1970s–1990s, it appears that pornography consumption is now irrelevant to sexism rather than promoting egalitarianism. Our analyses focusing on "pornography tolerance" revealed that people who supported regulated pornography were more egalitarian than people who supported a pornography ban. Generally, men were more likely to report sexist attitudes than women, but sex moderated the relationship that pornography variables had with sexism in several of the models. Overall, pornography consumption and pornography tolerance were either irrelevant in predicting sexism or were associated with greater egalitarianism.